Strategi Komunikasi Polres Menangani Hoax di Media Sosial melalui CPR - Artianasari, Nining; Qadaruddin, Muhammad (LP2M IAIN Palopo, 2022)
This study on Parepare Police Communication Strategy in dealing with the spread of fake news (Hoax) on Social Media through CPR (Cyber Public Relations). This research is based on the increasing number of hoax reports that occur in cyberspace, it is necessary to have an action from the apparatus and law enforcers, especially the police, to overcome this. One of the innovative steps that have been taken by the public relation s division of the Parepare Police, is to carry out severly stages of handling hoaxes. In the midst of an era of digital communication and information exchange, the use of online communication media in the public realtions process is an absolute must. In implementing good cyber public relations, it is necessary to have the right strategy which is considered effective and efficient which can be the key to the success of prorgams related to opinion management in cyberspace, including regarding fake news (Hoax). The purpose of this research was to provide a detail description of the communication startegies used by the Police of the City of Parepare in the context of Communication Studies, espesially cyber public relation in the dealing with hoaxes on social media. This research used a qualitative approach with a case study method. The findings of this study were that the Public Relations of Parepare Police in handling hoaxes used four public relations processes from Cutlip which consist of Fact, Finding, Planning Communication and Evaluation.